Party loyalty at referenda and general elections: evidence from recent Irish contests - McCarthy, C.; Ryan, T. (Economic & Social Studies, 1976)
The paper explores the extent of voter loyalty to party at different kinds of electoral contest. Voter transition matrices are computed using an estimation technique based on a quadratic programming algorithm. The data come from recent referenda, General and Presidential Elections in the Republic of Ireland and some strong patterns are evident in the results. A large group of voters consistently abstains and loyalty to party seems higher at General Elections than at referenda or Presidential contests.
Keywords: Politics; Voter Loyalty; Ireland